UPAYA PENCEGAHAN DAN PENANGANAN KEKERASAN PEREMPUAN DAN ANAK DALAM LINGKUP RUMAH TANGGA - Nurma Arianty Siregar; Listyaningsih Listyaningsih (Kajian Moral dan Kewarganegaraan, 2022)
Abstract This study aims to describe how the efforts to prevent and handle violence against women and children in the household sphere by the Social Service for Women's Empowerment and Child Protection in Madiun City in 2019- 2020. The theory used in this study is the theory of crime prevention proposed by G.F Hoefnagels. This research applies a qualitative approach with the type of case study research. Collecting data by conducting in depth interviews with informants observing, direct tracing and supporting data in the form of an annual book on cases of violence against women and children from the Sosial Service for Women’s Empowerment and Child Protection in Madiun City. The results of this study indicate that domestic violence (KDRT) against women and children is a problem that so far has not found a solution. The Social Service for Women’s Empowerment and Child Protection in Madiun City has implemented a number of preventive measure by conducting outreach to groups of adults and children. The purpose of socialization is to provide an overview of danger of domestic violence, so it is hoped that victims or the community can increase their awareness to report acts of domestict violence. Meanwhile, the handling way to against domestic violence did by establishing an Integrated Service Center (PPT) which specifically handles complaints of domestic violence against women and children, through : (1) direct complaints; (2) indirect complaints; (3) outreach; (4) referrals as follow-up handling victims; (5) and monitoring of referred victims. Keywords : prevention, treatment, violence against women, children.